Idiopathic pulmonary arterial hypertension phenotypes determined by cluster analysis from the COMPERA registry - Hoeper, Marius M; Pausch, Christine; Grünig, Ekkehard; Klose, Hans; Staehler, Gerd; Huscher, Doerte; Pittrow, David; Olsson, Karen M; Vizza, Carmine Dario; Gall, Henning; Benjamin, Nicola; Distler, Oliver; et al. (The Journal of heart and lung transplantation, 2020)
The term idiopathic pulmonary arterial hypertension (IPAH) is used to categorize patients with pre-capillary pulmonary hypertension of unknown origin. There is considerable variability in the clinical presentation of these patients. Using data from the Comparative, Prospective Registry of Newly Initiated Therapies for Pulmonary Hypertension, we performed a cluster analysis of 841 patients with IPAH based on age, sex, diffusion capacity of the lung for carbon monoxide (DLCO; <45% vs ≥45% predicted), smoking status, and presence of comorbidities (obesity, hypertension, coronary heart disease, and diabetes mellitus). A hierarchical agglomerative clustering algorithm was performed using Ward's minimum variance method. The clusters were analyzed in terms of baseline characteristics; survival; and response to pulmonary arterial hypertension (PAH) therapy, expressed as changes from baseline to follow-up in functional class, 6-minute walking distance, cardiac biomarkers, and risk. Three clusters were identified: Cluster 1 (n = 106; 12.6%): median age 45 years, 76% females, no comorbidities, mostly never smokers, DLCO ≥45%; Cluster 2 (n = 301; 35.8%): median age 75 years, 98% females, frequent comorbidities, no smoking history, DLCO mostly ≥45%; and Cluster 3 (n = 434; 51.6%): median age 72 years, 72% males, frequent comorbidities, history of smoking, and low DLCO. Patients in Cluster 1 had a better response to PAH treatment than patients in the 2 other clusters. Survival over 5 years was 84.6% in Cluster 1, 59.2% in Cluster 2, and 42.2% in Cluster 3 (unadjusted p < 0.001 for comparison between all groups). The population of patients diagnosed with IPAH is heterogenous. This cluster analysis identified distinct phenotypes, which differed in clinical presentation, response to therapy, and survival.